Physicochemical and Sensory Properties of Low Calory Salad Dressing from Jasmine Rice Bran Oil Extract - Duangsa, Boonyabhorn; Khumpumuang, Patcharida; Rodpon, Porntip; Rattanajun, Phimnipha; Jangkloy, Usana; Thiamjite, Piyamaporn; Jampatesh, Surawee; Rohhana, Katemanee; Sawisit, Apichai (Journal of Food Technology, Siam University, 2023)
This research aimed to report the physicochemical and sensory properties of salad dressing prepared using jasmine rice bran oil from Thung Kula Rong Hai, Roi Et Province. The study investigated various factors, including the type of stabilizing agents (xanthan gum, guar gum, arabic gum, carboxymethyl cellulose (CMC) and pectin) at a concentration of 0.66%, the quantity of rice bran oil at 10-30%, and the type of sweeteners (fructose, monk fruit sweetener, sucralose, erythritol and stevia) to produce a low-fat salad dressing that closely matches commercially available options and is acceptable to consumers. The study found that using CMC resulted in the highest quality of rice bran oil salad dressing. When studying the appropriate quantity of CMC (0.0-0.83), it was determined that a salad formula with 0.5% CMC had the highest overall quality. Regarding the quantity of rice bran oil, it was found that using 15% did not significantly differ from using 20% in terms of quality. Therefore, 15% was chosen to produce a low-fat salad dressing that uses less oil while maintaining quality and consumer acceptance. Monk fruit sweetener was identified as a suitable alternative to fructose, with comparable quality and consumer acceptance. Notably, monk fruit sweetener serves as a zero-calorie sugar substitute, making it an excellent choice for health-conscious consumers. A salad dressing with physicochemical and sensory properties similar to commercial options can be created using a 15:15:0.5% (by weight) ratio of rice bran oil, monk fruit sweetener, and CMC. This formulation is well-suited for producing salad dressings that cater to health-conscious consumers in the future.